Study the usage of rotifer (Brachionus plicatilis ) Qualitative and Quantitative Study of Sturgeon finger lings fram the time of production up to their releas - Alizadeh, Mahdi; Mohseni, M.; PourAli, H.R.; Mohammadi Pareshkohi, H.; Shenavar, A.R.; Jalilpour, J.; Masoamzadeh, M.; Bazarimoghaddam, S.; Fadaei, B.; Bahrouz Khoshghalb, M.R.; Tarakoli, M.; Joshideh, H. (Iranian Fisheries Science Research Institute, 2005)
The present study that was conducted in collaboration with the departments of fish breeding and rearing, pathology and stock assessment of the International Sturgeon Research Institute at the Shahid Beheshti hatchery commenced on 26 February 2002 and ended on 7 June 2002 simultaneously with the breeding of beluga breeders. About 230 sturgeon specimens were studied of which 176 belonged to A. persicus spawners (103 females used for artificial breeding, 16 females not used for artificial breeding and 57 males), 46 A. stellatus spawners (13 females used for artificial breeding, 20 females not used for artificial breeding and 13 males), 3 A. nudiventris spawners and five H. huso female spawners. The total length of A. persicus spawners used for artificial breeding ranged from 131.5 to 211 cm with an average length of 172.5 cm and their weight ranged from 14 to 49 Kg. The minimum and maximum weight of eggs was 9 and 1.5 Kg, respectively and the minimum and maximum number of eggs per gram was 46 and 67 eggs, respectively. The maximum condition factor for spawners was 0.94 and the minimum condition factor was 0.49 (average 0.74). The age of spawners ranged from 12 to 20 years and the minimum and maximum time taken by spawners to respond to breeding was 293.8 and 486 t?. The GV1 in these breeders ranged from 6.2 to 17.5 and GV2 ranged from 5.3 to 9.3. The maximum fertilization rate was 100 %. The total length of A. persicus breeders that were not used in artificial breeding ranged from 152 to 203 cm and their weight ranged from 14 to 46 Kg. The minimum and maximum weight of eggs was 3.2 and 8.5 Kg, respectively and the minimum and maximum number of eggs per gram was 46 and 64 eggs, respectively. The maximum condition factor for spawners was 0.81 and the minimum condition factor was 0.39 (average 0.69). The age of spawners ranged from 16 to 19 years. The GV1 in these breeders ranged from 7.8 to 16.3 and GV2 ranged from 6.5 to 8.2. Total length of male A. persicus breeders ranged from 129 to 178 cm and their weight ranged ...